Analisis Dampak Dan Perlindungan Terhadap Fenomena Kasus Pemerkosaan - Anya Forger (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2023)
The percentage of crimes that occur in Indonesia is increasing day by day, especially regarding rape cases. This phenomenon is very much discussed in society, especially cases of rape against teenagers and even minors or children. The majority of these rape cases are young girls. Rape has the characteristic of unwanted coercive behavior and has a detrimental effect on the victim. Which is where the victim can be sure to be damaged in terms of the good things that the victim dreams of in the future. The incident of rape can also make the victim afraid and even traumatized by her own thoughts, for example the victim thinks she is no longer good. Not to mention that the victim has to face the social stigma and discrimination that causes the victim's mental state to be down.